Environmental performance of bamboo fibers and sugarcane bagasse reinforced metakaolin-based geopolymers - Ariel Riofrio (Case Studies in Construction Materials, 2022)
Global warming and greenhouse gas emissions are significant concerns of the modern world. The cement industry causes 5–7% of CO2 gas emissions. Despite this critical environmental burden, cement is needed to develop future societies. Geopolymers are an alternative that has significantly fewer emissions than Ordinary Portland Cement. A geopolymer that considers the inclusion of natural fibers (bamboo and sugar cane bagasse) was developed. Two pre-treatments were considered for the fibers to remove lignin and starch. A life cycle assessment was performed on this geopolymer composite to evaluate its performance and compare the environmental impact of other options. The low liquid ammonia treated sugar cane bagasse fiber geopolymer had a better environmental performance with 857.9 kg CO2 eq per 1 m3 of pure binder (no aggregates). The other fiber alternatives had 2–4% more CO2 emissions. The geopolymer had excellent impact scores compared to different options and current OPC. The sensitivity analysis showed a concise and complete system that varies slightly when variables could provide uncertainty.